2015
DOI: 10.1080/15438627.2015.1040916
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Management Strategy and Performance in an Extreme Mountain Ultra-marathon

Abstract: We intended to assess the relationship between sleep strategies and performance during the North-Face Ultra-Trail du Mont-Blanc 2013, to test the hypothesis that sleep management can influence athletic performance. Almost all runners specifically adopted sleep management strategies before the race. Among the finishers 72% didn't sleep at all during the race and 28% took a least one break for sleep. Non-sleepers completed the race faster than the sleepers (P = 0.0008). Race time was positively correlated with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
1
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(65 citation statements)
references
References 14 publications
3
55
1
6
Order By: Relevance
“…Despite increased isometric exercise performance and lower RPE with sleep extension vs normal sleep, neuromuscular parameters were not different between the two conditions. The positive effect of greater sleep time on exercise performance is supported by findings from UTMB where runners that slept longer the night before the race had faster finishing times than the runners that did not (Poussel et al 2015). Another relevant study occurred in conjunction with TdG.…”
Section: Sleep Deprivationmentioning
confidence: 83%
See 2 more Smart Citations
“…Despite increased isometric exercise performance and lower RPE with sleep extension vs normal sleep, neuromuscular parameters were not different between the two conditions. The positive effect of greater sleep time on exercise performance is supported by findings from UTMB where runners that slept longer the night before the race had faster finishing times than the runners that did not (Poussel et al 2015). Another relevant study occurred in conjunction with TdG.…”
Section: Sleep Deprivationmentioning
confidence: 83%
“…In ultra-endurance exercise bouts, this may present as either complete (i.e. no sleep) or partial (some sleep) sleep deprivation, depending on the duration of the ultra-endurance event or experience or sleep strategy of the athlete (Poussel et al 2015). Individuals experiencing sleep deprivation often report subjective feelings of tiredness, clumsiness and fatigue.…”
Section: Sleep Deprivationmentioning
confidence: 99%
See 1 more Smart Citation
“…This ultra-endurance discipline is extremely challenging, and runners must deal with environmental and meteorological conditions, altitude changes, the topography of the terrain, the onset of pain and fatigue, muscular damage (e.g., Schmidt Easthope et al, 2010), exhaustion and effects due to sleep deprivation (e.g., Hurdiel et al, 2015; Poussel et al, 2015). Furthermore, Nicolas et al (2011) showed that runners’ perceptions of stress after a 24-h ultra-marathon alter their psychological recovery.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of extreme fatigue induced via sleep deprivation were studied in a sample of mountain ultra-marathon runners (Poussel et al, 2015). Runners who adopted a sleep-management strategy of increasing sleep time a few days before the race finished faster on average.…”
Section: Physiologicalmentioning
confidence: 99%